The larva, pupa, and female and male genitalia of Aedes (Howardina) guatemala Berlin, 1969 (Diptera: Culicidae) - Viveros-Santos, Vicente; Rivera-García, Karina D.; Ibáñez-Bernal, Sergio (Zootaxa, 2023)
Aedes (Howardina) guatemala Berlin, 1969 was recently recorded in Mexico. Based on material collected in Chiapas State, the larva, pupa, and female and male genitalia of this species are described for the first time.